ANALISIS KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM IMPLEMENTASI STANDAR NASIONAL PENDIDIKAN : PERSPEKTIF HASIL ASESMEN BERBASIS KINERJA - Lilik Hidayat Pulungan (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to analyze principals' managerial competence in implementing National Education Standards from a performance-based assessment perspective. This article employs a Systematic Literature Review method by examining relevant scientific publications related to school leadership, principals' managerial competence, education quality standards, and performance assessment. The findings indicate that principals' managerial competence plays a strategic role in achieving national education standards through data-driven planning, resource management, quality culture development, and continuous evaluation. The novelty of this study lies in integrating performance-based assessment as an approach to evaluating principals' managerial competence beyond administrative performance toward transformational school improvement. The study provides implications for strengthening professional development programs and educational quality policies